PENERAPAN METODE SAW DALAM MENENTUKAN KEPUTUSAN SUSPEK POSITIF COVID-19 - Hardianto, Roki; Heleni Filtri; Eddissyah Putra Pane; Sukma RA, Dodi; Sutejo (ZONAsi: Jurnal Sistem Informasi, 2023)
Research on Decision Support Systems that can detect symptoms of positive Covid-19 patients. This study aims to help health workers apply IT in services to Covid-19 patients. Data taken from samples obtained directly from the Riau Provincial Health Office and Pekanbaru City Health Office and the official website of the National Covid-19 Management Agency. In this research, the team consists of the fields of computer science and psychology education in order to fulfill the aspects needed in improving the research results. The assessment aspect of the recommended criteria for Covid-19 tracing patients are 11 questions taken from the Riau Province Covid-19 website. The data is weighted and processed by SAW method Decision Support Systems. The results of the method processing is 3 decision recommendations that are indicated by Covid-19.